Molybdenum-fluorine double-doped high-nickel cobalt-free positive electrode material as well as preparation method and application thereof
By adopting the molybdenum-fluorine double-doping strategy in high-nickel cobalt-free cathode materials, the irreversible phase change process is alleviated, and the shortcomings of the cathode materials of lithium-ion batteries in terms of energy density, safety and environmental protection are solved, and the effects of high capacity, excellent cycling performance and low production cost are achieved.
Patent Information
- Application Number
- CN202411954258.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing lithium-ion battery positive electrode materials have shortcomings in terms of energy density, safety and environmental protection, especially high-nickel cobalt-manganese ternary materials are difficult to widely use due to scarce cobalt resources, expensive and low safety.
Using the molybdenum-fluorine dual-doping strategy, a high-nickel cobalt-free cathode material LiaNixMnyMo1-x-yFzOb, which is double-doped with molybdenum-fluorine dual-doped, is developed. Through the doping of Mo and F, the irreversible phase change process of the high-nickel cobalt-free cathode material under high cutoff voltage is alleviated, and its cyclic stability and rate performance are improved.
The high capacity, excellent circulation performance and low production cost of high nickel cobalt-free cathode materials are achieved, and the circulation performance, capacity and thermal stability of lithium-ion batteries are significantly improved.
Smart Images

Figure CN119852391A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy storage technology, and relates to a lithium-ion battery positive electrode material and a preparation method and application thereof, and in particular to a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium secondary batteries have been widely used in consumer electronics, electric vehicles, and energy storage due to their advantages of high discharge capacity and long cycle life. However, with the rapid development of social economy, people have put forward higher requirements on power batteries in terms of energy density, safety, and environmental protection. As a key component of lithium-ion batteries, positive electrode materials have always been the focus of research. Among the currently commercialized layered positive electrode materials, lithium cobalt oxide (LiCoO 2 ) has become one of the earliest materials to achieve full commercialization due to its simple synthesis process and excellent cycle performance. However, its capacity density is low and can no longer meet current needs. In contrast, high nickel cobalt manganese ternary materials (such as NCM811) have become the most promising positive electrode materials in the field of electric vehicles due to their higher energy density. However, due to the scarcity of global cobalt resources, high prices, radioactive environmental pollution problems and low safety, its widespread application still faces many challenges.
[0003] The present invention aims to solve the problems existing in the current positive electrode materials of lithium-ion batteries and develop a new material system with both high capacity and excellent cycle performance. In order to make the high-nickel cobalt-free material have better cycle stability and rate performance and reduce the degree of lithium-nickel mixing, a dual doping strategy of molybdenum and fluorine anions and cations is adopted, thereby further reducing the production cost of the high-nickel cobalt-free positive electrode material and greatly improving the lithium storage performance of the high-nickel cobalt-free material. Summary of the invention
[0004] The purpose of the present invention is to develop a new type of high-nickel cobalt-free material system with high capacity and excellent cycle performance in view of the problems existing in the current positive electrode materials of lithium-ion batteries. In order to make the high-nickel cobalt-free positive electrode material have better cycle stability and rate performance, reduce the degree of lithium-nickel mixing, and reduce the production cost of the high-nickel positive electrode material, a strategy of molybdenum and fluorine anion and cation dual doping is adopted, thereby further reducing the production cost of the high-nickel positive electrode material and greatly improving the lithium storage performance of the high-nickel cobalt-free material.
[0005] The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material Li a Ni x Mn y Mo 1-x-y F z O bAmong them, 1≤a≤1.2, 1.9≤b≤2.1, 0.75≤x≤0.8, 0.02≤y≤0.2, 0.01≤z≤0.03, and dual doping of Mo and F can alleviate the irreversible phase change process of high-nickel cobalt-free positive electrode materials at high cut-off voltage, which can not only improve the first coulombic efficiency (96.9%), but also improve its cycle life (after 100 cycles, a discharge specific capacity of 116.2mAh / g and a capacity retention rate of 99.08% were achieved).
[0006] In order to achieve the above object, the technical solution adopted by the present invention to achieve the object is:
[0007] A molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, characterized in that Li a Ni x Mn y Mo 1-x-y F z O b Among them, 1≤a≤1.2, 1.9≤b≤2.1, 0.75≤x≤0.8, 0.02≤y≤0.2, 0.01≤z≤0.03.
[0008] In order to achieve the above object, another technical solution adopted by the present invention to achieve the object is:
[0009] A method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material comprises the following steps:
[0010] Step 1: Add nickel salt and manganese salt into deionized water in a molar mass ratio of (0.801-0.899):(0.101-0.199) and stir continuously to obtain solution A;
[0011] Step 2: Mix ammonia water (ammonia content of 25-28%) and deionized water in a volume ratio of (0.1-0.6):1 and stir continuously for 60 minutes to obtain an ammonia solution;
[0012] Step 3: Solution A was slowly added to the ammonia solution at a rate of 0.1-0.8 mL / min through a peristaltic pump. Under nitrogen protection, the mixture was stirred at a speed of 500-1000 rpm. At the same time, a 1-5 mol L -1 The sodium hydroxide solution is added, and the pH of the mixed solution is ensured to be between 10.2 and 11.6. The temperature of the whole system is between 40 and 80 ° C. After continuous stirring for 24 to 48 hours, it is allowed to stand at room temperature for 4 to 12 hours. After centrifugation, washing and drying, the precursor Ni of the nickel-manganese binary material is obtained. x Mn 1-x (OH) 2 , where 0.79≤x≤0.99;
[0013] Step 4: Ni precursor x Mn 1-x (OH) 2 : molybdenum oxide: ammonium fluoride: lithium salt in a molar ratio of 1: (0.05-0.09): (0.03-0.05): (1.01-1.08) were mixed and ground for 30-60 minutes, and then heated at a rate of 1.0-3.0°C / min in O 2 After being kept at 850-1000°C for 10-20h in an atmosphere, the mixture is naturally cooled to room temperature to obtain a high-nickel cobalt-free positive electrode material Li with surface Mo enrichment and molybdenum-fluorine dual doping. a Ni x Mn y Mo 1-x-y F z O b Among them, 1≤a≤1.2, 1.9≤b≤2.1, 0.75≤x≤0.8, 0.02≤y≤0.2, 0.01≤z≤0.03.
[0014] Further preferably, in step (1), the nickel salt is any one of nickel sulfate, nickel chloride and nickel nitrate.
[0015] More preferably, in step (1), the nickel salt is any one of manganese sulfate, manganese chloride and manganese nitrate.
[0016] More preferably, in step (4), the lithium salt is any one of lithium hydroxide, lithium carbonate and lithium acetate.
[0017] An application of a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, characterized by being used as a positive electrode material for lithium-ion batteries. Specifically applied to CR2032 button-type lithium-ion batteries, the method comprises the following steps:
[0018] (a) mixing high-nickel cobalt-free composite material: Ketjen black: polyvinylidene fluoride according to a mass ratio of (6-8): (3-1): 1, stirring evenly to obtain a solid mixture;
[0019] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 1:(3-4), stirring evenly, and preparing a slurry;
[0020] (c) coating the slurry obtained in step (b) on a copper foil, and preparing a lithium ion battery electrode sheet with a thickness of 13 to 22 μm after drying and rolling;
[0021] (d) The lithium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, a microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF6 The mixture was used as the electrolyte and assembled into CR2032 button lithium-ion batteries in a glove box filled with argon.
[0022] The advantages and beneficial effects of the present invention are as follows: the present invention combines the advantages of high capacity, good safety, low cost, etc. of the high-nickel cobalt-free positive electrode material itself, and further optimizes the lithium ion transmission channel structure by using Mo and F dual doping, reduces the lithium-nickel mixed arrangement phenomenon, and increases the diffusion rate of lithium ions, thereby improving the rate performance. Therefore, when the molybdenum-fluorine dual doped high-nickel cobalt-free positive electrode material obtained by combining the above effects is used in lithium-ion batteries, it can greatly improve the cycle performance, capacity and thermal stability of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material Ni prepared in Example 1 of the present invention 0.8 Mn 0.2 (OH) 2 Scanning electron microscope (SEM) image of the precursor.
[0024] Figure 2 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.8 Mn 0.2 O 2 Scanning electron microscope (SEM) image.
[0025] Figure 3 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 Scanning electron microscope (SEM) image.
[0026] Figure 4 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 Scanning transmission electron microscopy (STEM) image.
[0027] Figure 5 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi doped with Mo and F 0.75 Mn 0.2 Mo 0.05 F0.03 O 1.97 (abbreviated as MF-NM) X-ray diffraction (XRD) pattern.
[0028] Figure 6 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi doped with Mo and F 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM) as a positive electrode material for lithium-ion batteries at 3.0C (1C = 200 mAh g -1 ) after 100 cycles.
[0029] Figure 7 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 of the present invention 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi doped with Mo and F 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM) as a positive electrode material for lithium-ion batteries at 3.0C (1C = 200 mAh g -1 ) for each of the 100 cycles. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to more fully understand the present invention, the preferred embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with examples.
[0031] Example 1
[0032] 1. A method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, specifically comprising the following steps:
[0033] (1) Weigh 12.45 g of nickel sulfate and 0.25 g of manganese sulfate respectively and dissolve them in 25 mL of deionized water. Stir until fully dissolved to obtain solution A.
[0034] (2) 5.0 mL of ammonia water (ammonia content of 25-28%) and 75.0 mL of deionized water were respectively measured and mixed to prepare an ammonia solution, which was continuously stirred and heated to 60°C.
[0035] (3) Solution A was slowly added dropwise to the ammonia solution at a rate of 0.3 mL / min, and stirred continuously at a speed of 500-1000 rpm under nitrogen protection; at the same time, a 2.0 mol L -1 NaOH solution and ensure that the temperature of the whole system is 60 ° C, the pH of the mixed solution is 11.0, and after continuous stirring for 24 hours, it is allowed to stand at room temperature for 10 hours, and then centrifuged, washed, and dried to obtain the precursor Ni of the nickel-manganese binary material. 0.8 Mn 0.2 (OH) 2 ;
[0036] (4) 0.51 g of precursor Ni 0.8 Mn 0.2 (OH) 2 , 0.12 g of molybdenum oxide, 0.06 g of ammonium fluoride and 0.24 g of lithium hydroxide were mixed and ground for 60 min at a heating rate of 2.5 °C / min in O 2 After being kept at 1000 °C for 16 h in an atmosphere, the mixture was naturally cooled to room temperature to obtain a molybdenum-fluorine doped high-nickel cobalt-free cathode material LiNi 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM); at the same time, 0.51g of precursor Ni 0.8 Mn 0.2 (OH) 2 and 0.24 g lithium hydroxide, mixed and ground for 60 min, and heated at a rate of 2.5 °C / min in O 2 After being kept at 1000°C for 16 hours in an atmosphere, it was naturally cooled to room temperature to obtain the high-nickel cobalt-free positive electrode material LiNi 0.8 Mn 0.2 O 2 (Abbreviated as NM).
[0037] 2. A method for applying a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material to a CR2032 button-type lithium-ion battery, comprising the following steps:
[0038] (a) mixing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, polyvinylidene fluoride, and Ketjen black in a mass ratio of 8:1:1 to obtain a solid mixture;
[0039] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 25:75, stirring evenly, to obtain a slurry;
[0040] (c) coating the slurry obtained in step (b) on an aluminum foil, and preparing a lithium ion battery electrode sheet with a thickness of 10 to 24 μm after drying and rolling;
[0041] (d) The lithium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, the lithium sheet is used as the positive electrode sheet, a microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF 6 and solvent as electrolyte, and assembled into CR2032 button lithium-ion batteries in a glove box filled with argon.
[0042] (e) Testing the lithium-ion battery assembled in step (d) at a voltage of 2.8 to 4.3 V and a test temperature of 25° C.
[0043] Example 2
[0044] 1. A method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, specifically comprising the following steps:
[0045] (1) Weigh 11.0 g of nickel chloride and 0.36 g of manganese chloride respectively and dissolve them in 25 mL of deionized water. Stir until fully dissolved to obtain solution A.
[0046] (2) 9.4 mL of ammonia water (ammonia content of 25-28%) and 90.6 mL of deionized water were respectively measured and mixed to prepare 100 mL of ammonia solution, which was continuously stirred and heated to 70°C.
[0047] (3) Solution A was slowly added dropwise to the ammonia solution at a rate of 0.1 mL / min, and stirred continuously at a speed of 500-1000 rpm under nitrogen protection; at the same time, a 4.0 mol L -1 NaOH solution and ensure that the temperature of the whole system is 60 ° C, the pH of the mixed solution is 11.6, and after continuous stirring for 24 hours, it is allowed to stand at room temperature for 10 hours, and then centrifuged, washed, and dried to obtain the precursor Ni of the nickel-manganese binary material. 0.85 Mn 0.15 (OH) 2 ;
[0048] (4) 0.53 g of precursor Ni 0.85 Mn 0.15 (OH) 2 , 0.19 g of molybdenum oxide, 0.03 g of ammonium fluoride and 0.35 g of lithium hydroxide were mixed and ground for 60 min at a heating rate of 2.5 °C / min in O 2After being kept at 950 °C for 16 h in an atmosphere, the material was naturally cooled to room temperature to obtain a molybdenum-fluorine doped high-nickel cobalt-free cathode material Li 1.2 Ni 0.80 Mn 0.19 Mo 0.01 F 0.01 O 2 .
[0049] 2. A method for applying a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material to a CR2032 button-type lithium-ion battery, comprising the following steps:
[0050] (a) mixing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, polyvinylidene fluoride, and Ketjen black in a mass ratio of 6:2:2 to obtain a solid mixture;
[0051] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 25:75, stirring evenly, to obtain a slurry;
[0052] (c) coating the slurry obtained in step (b) on an aluminum foil, and preparing a lithium ion battery electrode sheet with a thickness of 10 to 24 μm after drying and rolling;
[0053] (d) The lithium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, the lithium sheet is used as the positive electrode sheet, a microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF 6 and solvent as electrolyte, and assembled into CR2032 button lithium-ion batteries in a glove box filled with argon.
[0054] (e) Testing the lithium-ion battery assembled in step (d) at a voltage of 2.8 to 4.3 V and a test temperature of 25° C.
[0055] Example 3
[0056] 1. A method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, specifically comprising the following steps:
[0057] (1) Weigh 11.17 g of nickel nitrate and 0.37 g of manganese nitrate respectively and dissolve them in 25 mL of deionized water. Stir until fully dissolved to obtain solution A.
[0058] (2) 34.5 mL of ammonia water (ammonia content of 25-28%) and 65.5 mL of deionized water were respectively measured and mixed to prepare 100 mL of ammonia solution, which was continuously stirred and heated to 80°C.
[0059] (3) Solution A was slowly added dropwise to the ammonia solution at a rate of 0.1 mL / min, and stirred continuously at a speed of 500-1000 rpm under nitrogen protection; at the same time, a 4 mol L -1 NaOH solution and ensure that the temperature of the whole system is 60 ° C, the pH of the mixed solution is 10.2, and after continuous stirring for 24 hours, it is allowed to stand at room temperature for 10 hours, and then centrifuged, washed, and dried to obtain the precursor Ni of the nickel-manganese binary material. 0.83 Mn 0.17 (OH) 2 ;
[0060] (4) 0.59 g of precursor Ni 0.8 Mn 0.2 (OH) 2 , 0.22 g of molybdenum oxide, 0.04 g of ammonium fluoride and 0.28 g of lithium hydroxide were mixed and ground for 60 min at a heating rate of 2.5 °C / min in O 2 After being kept at 850 ° C for 16 h in an atmosphere, it was naturally cooled to room temperature to obtain a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material Li 1.1 Ni 0.81 Mn 0.15 Mo 0.04 F 0.02 O 1.95 .
[0061] 2. A method for applying a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material to a CR2032 button-type lithium-ion battery, comprising the following steps:
[0062] (a) mixing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, polyvinylidene fluoride, and Ketjen black in a mass ratio of 95:2.5:2.5 to obtain a solid mixture;
[0063] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 25:75, stirring evenly, to obtain a slurry;
[0064] (c) coating the slurry obtained in step (b) on an aluminum foil, and preparing a lithium ion battery electrode sheet with a thickness of 10 to 24 μm after drying and rolling;
[0065] (d) The lithium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, the lithium sheet is used as the positive electrode sheet, a microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF 6 and solvent as electrolyte, and assembled into CR2032 button lithium-ion batteries in a glove box filled with argon.
[0066] (e) Testing the lithium-ion battery assembled in step (d) at a voltage of 2.8 to 4.3 V and a test temperature of 25° C.
[0067] Example 4
[0068] 1. A method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, specifically comprising the following steps:
[0069] (1) Weigh 10.56 g of nickel sulfate and 0.16 g of manganese sulfate respectively and dissolve them in 25 mL of deionized water. Stir until fully dissolved to obtain solution A.
[0070] (2) Separately measure 17.5 mL of ammonia water (ammonia content of 25-28%) and 82.5 mL of deionized water to mix into 100 mL of ammonia solution, stir continuously and heat to 60°C.
[0071] (3) Solution A was slowly added dropwise to the ammonia solution at a rate of 0.1 mL / min, and stirred continuously at a speed of 500-1000 rpm under nitrogen protection; at the same time, a 4 mol L -1 NaOH solution and ensure that the temperature of the whole system is 80 ° C, the pH of the mixed solution is 11.5, and after continuous stirring for 24 hours, it is allowed to stand at room temperature for 10 hours, and then centrifuged, washed, and dried to obtain the precursor Ni of the nickel-manganese binary material. 0.9 Mn 0.1 (OH) 2 ;
[0072] (4) 0.53 g of precursor Ni 0.9 Mn 0.1 (OH) 2 , 0.39 g of molybdenum oxide, 0.09 g of ammonium fluoride and 0.26 g of lithium carbonate were mixed and ground for 60 min at a heating rate of 2.5 °C / min in O 2 After being kept at 1000 °C for 20 h in an atmosphere, the mixture was naturally cooled to room temperature to obtain a molybdenum-fluorine doped high-nickel cobalt-free cathode material Li 1.05 Ni 0.85 Mn 0.1 Mo 0.05 F 0.01 O 2.1 .
[0073] 2. A method for applying a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material to a CR2032 button-type lithium-ion battery, comprising the following steps:
[0074] (a) mixing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, polyvinylidene fluoride, and Ketjen black in a mass ratio of 92.5:3.75:3.75 to obtain a solid mixture;
[0075] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 25:75, stirring evenly, to obtain a slurry;
[0076] (c) coating the slurry obtained in step (b) on an aluminum foil, and preparing a lithium ion battery electrode sheet with a thickness of 10 to 24 μm after drying and rolling;
[0077] (d) The lithium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, the lithium sheet is used as the positive electrode sheet, a microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF 6 and solvent as electrolyte, and assembled into CR2032 button lithium-ion batteries in a glove box filled with argon.
[0078] (e) Testing the lithium-ion battery assembled in step (d) at a voltage of 2.8 to 4.3 V and a test temperature of 25° C.
[0079] Figure 1 The Ni prepared in Example 1 0.8 Mn 0.2 (OH) 2 From the scanning electron microscope image of the high-nickel cobalt-free cathode material precursor, it can be seen that the secondary particles of the precursor are uniform and regular spherical with a diameter of about 3 to 5 μm.
[0080] Figure 2 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.8 Mn 0.2 O 2 The scanning electron microscope image shows the clear morphology of single crystal particles, with a particle size of about 2 to 3 μm. The material after calcination is partially broken and aggregated;
[0081] Figure 3 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 From the scanning electron microscope image, we can see the clear morphology of single crystal particles, with a particle size of about 2 to 3 μm. The particles of the doped material are uniform and have no agglomeration phenomenon;
[0082] Figure 4 The molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97STEM image. It can be seen that the material has a complete and uniform R-3m layered structure.
[0083] Figure 5 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM) XRD spectrum. It can be clearly seen that both materials show obvious LiNiO 2 R-3m space lattice group, which indicates that both materials have a complete crystal structure, and the peak of MF-NM shifts to a small angle, indicating that dual doping with Mo and F is beneficial to increase the lattice spacing, thereby facilitating lithium ion transport.
[0084] Figure 6 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM) as a positive electrode material for lithium-ion batteries at 3.0C (1C = 200mAh g -1 ) under the cycling performance diagram. The discharge capacity of MF-NM is still maintained at 116.2 mAh / g after 100 cycles, while the discharge capacity of NM is only 39.6 mAh / g after 100 cycles.
[0085] Figure 7 The high-nickel cobalt-free positive electrode material LiNi prepared in Example 1 0.8 Mn 0.2 O 2 (abbreviated as NM) and LiNi 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 (abbreviated as MF-NM) as a positive electrode material for lithium-ion batteries at 3.0C (1C = 200mAh g -1 ) for each of the 100 cycles. The Coulombic efficiency of NM is unstable and below 90%, while that of MF-NM is stable above 95%.
[0086] Molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material LiNi prepared in Examples 1-40.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 The lithium-ion battery performance results are shown in Table 1.
[0087] Table 1 shows the lithium ion batteries of Example 1, Example 2, Example 3 and Example 4 at 3.0C (1C = 200 mAh g -1 ) are the capacities obtained from the 2nd and 100th cycles of charge and discharge tests.
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 that the high nickel cobalt-free positive electrode material LiNi doped with molybdenum and fluorine according to the present invention 0.75 Mn 0.2 Mo 0.05 F 0.03 O 1.97 Applied to lithium-ion batteries, at a high rate of 3.0C, the charging capacity can still basically remain above 110mAh / g after 100 cycles, with excellent cycle performance, which is higher than the currently commercialized high-nickel positive electrode materials such as NCM811 and NCA622.
[0091] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material, characterized in that: The chemical formula of the molybdenum-fluorine doped high nickel cobalt-free positive electrode material is Li a Ni x Mn y Mo 1-x-y F z O b , wherein 1≤a≤1.2, 1.9≤b≤2.1, 0.75≤x≤0.8, 0.02≤y≤0.2, 0.01≤z≤0.03; the particle size of the molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material is 2 to 3 μm, and the material has an R-3m layered structure inside.
2. The method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The following steps are involved: Step 1: Add nickel salt and manganese salt into deionized water in a molar mass ratio of (0.801-0.899):(0.101-0.199) and stir continuously to obtain solution A; Step 2: Mix ammonia water (ammonia content of 25-28%) and deionized water in a volume ratio of (0.1-0.6):1 and stir continuously for 60 minutes to obtain an ammonia solution; Step 3: Solution A was slowly added to the ammonia solution at a rate of 0.1-0.8 mL / min through a peristaltic pump. Under nitrogen protection, the mixture was stirred continuously at a speed of 500-1000 rpm. At the same time, a 1-5 mol / L -1 The sodium hydroxide solution is added, and the temperature of the whole system is ensured to be between 40 and 80 ° C, and the pH of the mixed solution is between 10.2 and 11.
6. After continuous stirring for 24 to 48 hours, it is allowed to stand at room temperature for 4 to 12 hours, and then centrifuged, washed, and dried to obtain the precursor Ni of the nickel-manganese binary material. x Mn 1-x (OH)2, where 0.79≤x≤0.99; Step 4: Ni precursor x Mn 1-x (OH)2: molybdenum oxide: ammonium fluoride: lithium salt are mixed and ground in a molar ratio of 1: (0.05-0.09): (0.03-0.05): (1.01-1.08) for 30-60 minutes, and then kept at 850-1000°C for 10-20 hours at a heating rate of 1.0-3.0°C / min in an O2 atmosphere, and then naturally cooled to room temperature to obtain a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material Li a Ni x Mn y Mo 1-x-y F z O b , where 1≤a≤1.2, 1.9≤b≤2.1, 0.75≤x≤0.8, 0.02≤y≤0.2, 0.01≤z≤0.
03.
3. The method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: In step (1), the nickel salt is any one of nickel sulfate, nickel chloride and nickel nitrate.
4. The method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: In step (1), the manganese salt is any one of manganese sulfate, manganese chloride and manganese nitrate.
5. The method for preparing a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: In step (4), the lithium salt is any one of lithium hydroxide, lithium carbonate and lithium acetate.
6. The use of a molybdenum-fluorine dual-doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: Application as positive electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method for manganese solid solution anode material of lithium ion battery material
CN103606667A
Large scale preparation method of high-nickel cobalt-free precursor and cathode material
CN109970106A
High-nickel layered composite material and lithium ion battery positive electrode material prepared from same
CN111509214A
Cation and fluorine anion double-doped modified ternary positive electrode material and preparation method thereof
CN113299906A
Anion-cation co-doped high-nickel single-crystal ternary positive electrode material as well as preparation method and application thereof
CN113764658A